Regulatory Functions of Protein Tyrosine Phosphatase Receptor Type O in Immune Cells - Xie, Feiling; Dong, Hongmei; Zhang, Hao (Frontiers in Immunology, 2021)
The members of the protein tyrosine phosphatase (PTP) family are key regulators in multiple signal transduction pathways and therefore they play important roles in many cellular processes, including immune response. As a member of PTP family, protein tyrosine phosphatase receptor type O (PTPRO) belongs to the R3 receptor-like protein tyrosine phosphatases. The expression of PTPRO isoforms is tissue-specific and the truncated PTPRO (PTPROt) is mainly observed in hematopoietic cells, including B cells, T cells, macrophages and other immune cells. Therefore, PTPROt may play an important role in immune cells by affecting their growth, differentiation, activation and immune responses. In this review, we will focus on the regulatory roles and underlying molecular mechanisms of PTPRO/PTPROt in immune cells, including B cells, T cells, and macrophages.